Antibacterial Activities of Selected Pure Compounds Isolated from Gut Bacteria of Animals Living in Polluted Environments - Noor Akbar; Ruqaiyyah Siddiqui; Mazhar Iqbal; Naveed Ahmed Khan (MDPI AG, 2020)
Antibiotic resistance is a global threat to public health, further accelerated by the misuse of antibiotics in humans and animals. Our recent studies have shown that gut bacteria of animals living in polluted environments are a potential source of antibacterials. Gut bacteria of cockroaches, water monitor lizards and the turtle exhibited molecules such as curcumenol, docosanedioic acid, N-acyl-homoserine lactone, L-homotyrosine and Di-rhamnolipids. Using purified compounds, assays were performed to determine their antibacterial properties using serial dilution method, cytotoxic effects using lactate dehydrogenase release, and cell viability using MTT assay. The results revealed that the purified compounds exhibited significant antibacterial activities (p < 0.05) against selected Gram-negative (Pseudomonas aeruginosa) and Gram-positive bacteria (Streptococcus pyogenes) with effective MIC50 and MIC90 at µg concentrations, and with minimal effects on human cells as observed from LDH and MTT assays. These findings are significant and provide a basis for the rational development of therapeutic antibacterials. Future studies are needed to determine in vivo effects of the identified molecules together with their mode of action, which could lead to the development of novel antibacterial(s).